Optimization of xylose production from rice straw using response surface methodology (RSM) - Mohd Suhaimi, Mohd Noor (2010)
Rice straw is a source of xylose which can be used as a raw material for production of many ,high value products. Xylose is a pentose sugar formed from xylan, one of the substrate in hemicelluloses. The aim of this study is to optimize xylose production from rice straw by manipulating the agitation time, pH and substrate concentration using Response Surface Methodology (RSM) based on central composite design (CCD). Acid and alkaline hydrolysis method was used for pretreatment of rice straw to remove lignin compound. After pretreatment, hemicellulose was used to produce xylose using enzymatic hydrolysis method. The enzyme used for enzymatic hydrolysis was Thermomyces Lanuginosus xylanase to degraded xylose from hemicelluloses.Enzymatic hydrolysis of rice straw was performed at 45°C and 250 rpm using agitation time (2-12 hours), pH (2-10) and substrate concentration (0.1-1.1 mg/ml). The best conditions for agitation time, pH and substrate concentration were approximately 4 hours, 6 and 0.9 mg/ml respectively. These values were used for optimization process using RSM. The optimized conditions from RSM were 4.14 hours of agitation time, pH 6.14 and 0.89 mg/ml of substrate concentration which produce 29.517 mg/ml of xylose. Before optimization, the xylose concentration was 24.694 mg/ml which the production of xyiose was increased by 19.53%. As conclusion, the combination between agitation time, pH and substrate concentration can increase the production of xylose from rice straw.